1989
DOI: 10.1177/000348948909801113
|View full text |Cite
|
Sign up to set email alerts
|

Newer Technique of Laryngeal Reinnervation: Superior Laryngeal Nerve (Motor Branch) as a Driver of the Posterior Cricoarytenoid Muscle

Abstract: This report analyzes the experience gained using two different techniques to reinnervate the paralyzed vocal cord. In the neurotization group, the superior laryngeal nerve (SLN) motor branch-cricothyroid muscle pedicle was used to reinnervate the posterior cricoarytenoid muscle. In the direct nerve anastomosis group, the SLN was anastomosed to the abductor branch of the recurrent laryngeal nerve (RLN), and the ansa hypoglossi (AH) to the adductor branch of the RLN. A third group of animals (control) had the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The nerve muscle pedicle (NMP) technique which was popularized by Tucker [1] and used in the treatment of vocal fold paralysis in earlier studies, has been abandoned since other surgeons were unable to use the technique satisfactorily [2-4]. Electrophysiological, histological, and anatomical studies have shown that the phrenic nerve is the optimal transfer nerve for reinnervation of the PCA muscle in treating patients with BVFP [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…The nerve muscle pedicle (NMP) technique which was popularized by Tucker [1] and used in the treatment of vocal fold paralysis in earlier studies, has been abandoned since other surgeons were unable to use the technique satisfactorily [2-4]. Electrophysiological, histological, and anatomical studies have shown that the phrenic nerve is the optimal transfer nerve for reinnervation of the PCA muscle in treating patients with BVFP [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…Second, transection of the VN at the cervical level would lead to recurrent laryngeal nerve injury, which would result in hoarseness and even dyspnea because of the absence of movement on the affected side of the vocal cords [43] , [44] . However, these symptoms might be significantly improved by laryngeal reinnervation [45] , [46] . Third, 80%−90% of VN fibers are afferent (sensory) [30] , so only 10%−20% of the surface area of anastomosis would be motor fibers that could regenerate into the PN and reinnervate the diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ability of the external branch of the superior laryngeal nerve (EBSLN) to drive the PCA has been previously demonstrated in a feline model. 4,5 Here, we report the first two cases of selective reinnervation of the PCA utilizing the EBSLN with good postoperative results.…”
Section: Introductionmentioning
confidence: 92%